An LC-MS/MS method for quantitation of methylparaben, benzophenone, and pharmaceutical compounds from domestic wastewater - Barreiro, Juliana Cristina; Florentino, Anna Patrícya; Furlani, Izadora Liranço; Silva, Gustavo H. R.; Cass, Quezia Bezerra (Frontiers in Analytical Science, 2022)
An analytical method was developed to quantify a mixture of acetaminophen, metoprolol, methylparaben, carbamazepine, naproxen, estrone, estradiol, diclofenac, benzophenone, ibuprofen, progesterone and mefenamic acid from domestic wastewater samples. To match fast and efficient chromatographic separation for different classes of compounds, an automated scouting liquid chromatographic system was associated with the experimental design produced by the DryLab(R) software. The HLB cartridges were used for extraction of the analytes from the sample matrix followed by detection and quantitation by liquid chromatography-tandem mass spectrometry (LC-MS/MS). The lowest detection limits were found for acetaminophen and carbamazepine (0.625 pg L-1) and metoprolol (0.4 pg L-1).